PELATIHAN DIGITAL MARKETING UNTUK PENGEMBANGAN MEDIA PROMOSI BERSAMA WIRAUSAHA MAHASISWA - Widyo Subagyo; Dyah Wahyuningsih; Mukhadiono Mukhadiono (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Students or millennial generation with their enthusiasm and high degree of creativity are the basic capital to create an entrepreneurial mentality. Based on the Hootsuite's Wearesocial publication research that released in January 2019, the digital social media users in our country Republic of Indonesia is about 150 million or 56% of the total of population. The number increased from time to time and this is up 20% from the survey before did. Meanwhile, the gadget or smartphone users reach more than 130 million or about 48% of the Indonesia population. The huge population and the very fast growth of internet and telephone users in Indonesia are potentials modal for the enrich national digital economy.Community service aims to improve student entrepreneurship skills by utilizing digital media as a means for effective marketing and creating pioneering joint promotion media through social media. The targets are students and alumni of the Purwokerto Nursing Study Program who have an interest or start a business. Community service in the form of training on optimizing digital marketing and making product advertisements.Community Service Results: increased understanding of digital marketing is indicated by an average understanding score before training of 12.16 and a score after training of 19.00. Produced promotional media for student entrepreneurship and alumni in the form of an online store through Instagram media called k8mart.polkesmar with 76 follower accounts, formed at least 5 entrepreneurs and 10 pioneering entrepreneurs.